2010
DOI: 10.1016/j.pep.2010.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression and purification strategies for recombinant multi-protein oligomers: A case study of Mycobacterium tuberculosis σ/anti-σ factor protein complexes

Abstract: The function of a protein in a cell often involves coordinated interactions with one or several regulatory partners. It is thus imperative to characterize a protein both in isolation as well as in the context of its complex with an interacting partner. High resolution structural information determined by X-ray crystallography and Nuclear Magnetic Resonance offer the best route to characterize protein complexes. These techniques, however, require highly purified and homogenous protein samples at high concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…As the purified anti-factors are prone to aggregation, the purified substrates used in these experiments consisted of the ECF factor complexed with an anti-factor containing the degron at the C terminus. Coexpression and copurification of the /antifactor complexes significantly improves the yield of homogenous protein samples, as the or anti-factors in isolation are relatively unstable (29). The segment comprising the last three residues (9-11) of the ssrA degron was shown to interact with E. coli ClpX (19).…”
Section: Resultsmentioning
confidence: 99%
“…As the purified anti-factors are prone to aggregation, the purified substrates used in these experiments consisted of the ECF factor complexed with an anti-factor containing the degron at the C terminus. Coexpression and copurification of the /antifactor complexes significantly improves the yield of homogenous protein samples, as the or anti-factors in isolation are relatively unstable (29). The segment comprising the last three residues (9-11) of the ssrA degron was shown to interact with E. coli ClpX (19).…”
Section: Resultsmentioning
confidence: 99%
“…In order to avoid the problems resulting from the unequal solubility and stability of the two interacting partner proteins when overexpressed separately (Thakur et al, 2010), we examined the physical interaction between RpoE and ChrR by cloning both genes (rpoE-chrR) together in pET15b to coexpress (i) His-RpoE from the Shine-Dalgarno (SD) sequence of the vector and (ii) wild-type ChrR from its native SD sequence located at the 39 end of the rpoE. We observed that the amount of the two overexpressed and eluted proteins was unequal (Fig.…”
Section: Cotranscription Of Rpoe and Chrr Genes And Interaction Of Rmentioning
confidence: 99%
“…4b, ii and iii). Another Role of RpoE in A. brasilense co-expression study of sigma factors and anti-sigma factors has shown that the expression of the promoter distal gene is usually lower than the promoter proximal gene, resulting in a substoichiometric complex of the two co-expressed proteins (Thakur et al, 2010). Since only His-RpoE can directly bind to the Ni-NTA agarose, presence of ChrR along with His-RpoE in the eluted fraction indicates that ChrR formed a complex with RpoE (Fig.…”
Section: Cotranscription Of Rpoe and Chrr Genes And Interaction Of Rmentioning
confidence: 99%
“…RsdA is the cognate anti-σ factor for σ D and full-length σ D interacts with the cytosolic component of RsdA (30). Crystallization trials were performed to obtain crystals of full-length σ D and the ASD of RsdA (RsdA 1 − 80 ).…”
Section: Resultsmentioning
confidence: 99%